Manajemen Pengembangan Kurikulum di Diniyah Takmiliyah Awaliyah Al-Istiqomah Bandung - Ahmad Ghozali Panjaitan; Dwi Ajeng Maulidya Makalao; Chaerly Mirochina (JUMPA : Jurnal Manajemen Pendidikan, 2022)
Management Curriculum Development In Diniyah Takmiliyah Awaliyah Al-Istiqomah Bandung. This research aims to know how Curriculum Development Management at DTA Al-Istiqomah because it is interesting for us researchers to research DTA Al-Istiqomah which is DTA is simple but in the shade Ministry of Religion and has its curriculum collaborated with curriculum from the Ministry of Religion. This research uses a qualitative approach. The method used for data collection is a descriptive-analytical method developed for obtaining Management data Curriculum Development Diniyah Takmiliyah Awaliyah Al-Istiqomah. This study collects data from the Observation Method, Interview, and Documentation. The headmaster and Madrasah DTA Teachers conduct curriculum development planning activities. Curriculum development in learning is using the curriculum from the inception of DTA and collaborating with the curriculum provided by the Ministry of Religion. The curriculum used by DTA Al Istiqomah, namely three lessons of the curriculum used alone from its inception DTA Al Istiqomah: Fiqh Safinah (Yellow Book), Sharaf, Tasrifan. The six lessons from the Ministry of Religion are the Qur'an, Hadith, creed, morals, History of Islam, Fiqh, and Arabic. Implementation process curriculum development DTA Al Istiqomah is currently under development. During the evaluation process, Diniya Takmilyah Awaliya Al Istiqomah does not do activities to evaluate curriculum development. But DTA Al Istiqomah only assesses learning outcomes every day